Active packaging coating based on Ocimum basilicum seed mucilage and Hypericum perforatum extract: Preparation, characterization, application and modeling the preservation of ostrich meat - Mahsa Zamani Faradonbeh; Hassan Barzegar; Mohammad Hojjati; Behrooz Alizadeh Behbahani; Morteza Taki (Applied Food Research)
Fresh meat is prone to spoilage, resulting in health risks and financial losses. Research has explored various edible coatings infused with antioxidants and antibacterial agents to preserve meat freshness. The purpose of this research was therefore to create an innovative edible coating for ostrich meat slices using Ocimum basilicum seed mucilage (OBSM) infused with Hypericum perforatum extract (HPE). The phenolic profile, antioxidant, and antimicrobial properties of HPE were investigated. The HPE contained significant levels of phenolic (34.48 mg gallic acid/g) and flavonoids (15.44 mg quercetin/g) compounds, which included hyperforin, protopseudohypericin, and hypericin as the primary extract compounds. The HPE also demonstrated potent antimicrobial and antioxidant activities. The HPE (0, 0.5, 1.5, and 2.5 %) was combined with OBSM to coat the ostrich meat slices and stabilize their physicochemical, microbial, and sensory properties during storage (4 °C, 9 days). The samples coated with OBSM+2.5 %HPE showed lower counts of total viable count (6.20 vs. 7.46 log colony forming unit (CFU)/g), psychrotrophic (4.09 vs. 5.37 log CFU/g), coliform (3.08 vs. 3.62 log CFU/g), and fungi (2.33 vs. 3.36 log CFU/g). Additionally, the coated samples exhibited a lower total color difference and higher moisture content, hardness, and overall acceptance during storage. The comparative analysis revealed that Gaussian Process Regression (GPR) outperformed the Multilayer Perceptron (MLP) in terms of precision, demonstrating a superior ability to estimate the experimental data with minimal deviation. The findings of this study indicate that the OBSM+HPE-based edible coating was highly effective in improving the shelf-life of ostrich meat.